2022
DOI: 10.1007/s10071-022-01680-y
|View full text |Cite
|
Sign up to set email alerts
|

Through the looking glass: how do marked dolphins use mirrors and what does it mean?

Abstract: Mirror-guided self-inspection is seen as a cognitive hallmark purportedly indicating the existence of self-recognition. Only a few species of great apes have been reported to pass a standard mark test for mirror self-recognition in which animals attempt to touch a mark. In addition, evidence for passing the mark test was also reported for Asian elephants, two species of corvids, and a species of cleaner fish. Mirror self-recognition has also been claimed for bottlenose dolphins, using exposure of marked areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Certain animals, particularly higher primates and dolphins, have been shown to have evidence of self‐consciousness. A dolphin will spend more time looking at itself in the mirror if certain marks are placed on its head (Loth, Güntürkün and von Fersen 2022). Of course, the communication barrier is a challenging problem, but it might be possible to observe whether animals appear to have consciousness in some form as better methodologies are developed.…”
Section: Identity and Self‐consciousnessmentioning
confidence: 99%
“…Certain animals, particularly higher primates and dolphins, have been shown to have evidence of self‐consciousness. A dolphin will spend more time looking at itself in the mirror if certain marks are placed on its head (Loth, Güntürkün and von Fersen 2022). Of course, the communication barrier is a challenging problem, but it might be possible to observe whether animals appear to have consciousness in some form as better methodologies are developed.…”
Section: Identity and Self‐consciousnessmentioning
confidence: 99%
“…Marine mammals have lived in zoological facilities such as zoos, aquaria, and marine mammal parks for more than the past century. During that time, studies have suggested that at least some of these species possess complex cognitive and communicative abilities, including imitation [ 1 , 2 , 3 , 4 ]; metacognition [ 5 ]; mirror self-recognition [ 6 ]; vocally-coordinated cooperation [ 7 ]; the ability to learn symbols and basic syntax [ 8 , 9 , 10 ]; and decades-long memory [ 11 , 12 ]. Over this same time period, thanks to advances in veterinary knowledge and husbandry care, there has been significant and ongoing improvement in the physical welfare of these animals, as evidenced by increases in their health, longevity, and breeding success [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, a mark has to be applied in a spot that can be seen without the use of the mirror to confirm the subjects’ motivation to remove marks in general (Gallup and Anderson 2018 ). Humans, most great apes, elephants, dolphins and cleaner fish show MSR (Gallup 1970 ; Gallup et al 2011 ; Kohda et al 2019 ; 2022 ; Loth et al 2022 ; Plotnik et al 2006 ; Reiss and Marino 2001 ). The evidence from species other than humans and great apes has, however, led to controversial discussion (Gallup and Anderson 2018 ; 2020 ).…”
Section: Introductionmentioning
confidence: 99%